Prognostic significance of systemic immune-inflammation index in patients with ovarian cancer: a meta-analysis - Mao, Huaying; Yang, Fan (Frontiers in Oncology, 2023)
Background: The prognosis of several malignancies has been influenced by the systemic immune-inflammation index (SII); however, its association with the prognostic outcome of ovarian cancer (OC) remains controversial. The present meta-analysis focused on the systemic and comprehensive identification of the role of SII in predicting OC prognosis. Methods: We searched the Web of Science, PubMed, Cochrane Library, Embase, and China National Knowledge Infrastructure (CNKI) from inception until March 6, 2023. To predict the prognostic value of SII for overall survival (OS) and progression-free survival (PFS) in patients with OC, we calculated pooled hazard ratios (HRs) and corresponding 95% confidence intervals (CIs). Results: The meta-analysis included six studies involving 1546 patients. The combined results showed that a high SII was significantly associated with poor OS (HR=2.70, 95% CI=1.98–3.67, p<0.001) and poor PFS (HR=2.71, 95% CI=1.78–4.12, p<0.001) in OC patients. These results were confirmed using subgroup and sensitivity analyses. Conclusion: Our results concluded that a high SII significantly predicted poor OS and PFS in patients with OC. Therefore, it can be speculated that the SII may have an independent effect on the prognosis of OC.